Design and development of a magnetorheological shock absorber for automotive applications - Jamaluddin, Hishamuddin (Faculty of Mechanical Engineering, 2009)
The purpose of this research is to develop an indigenous Magnetorheological damper or shock absorber for automotive application especially to be fitted in passenger vehicle. The research involves the design and development of the MR damper prototype, which the design was considering an optimum number of coils winding for the prototype. The research works also involve the development of a new control algorithm for the prototype where the algorithm is used to control the operation of the MR damper prototype. The algorithm is also functioning as a tool to improve the performance of the MR damper prototype. The prototype, which was made in a tube form, is suitable to be applied in vehicle’s suspension system. A wider range of damping characteristic of the MR damper made it suitable to be assembled in any passenger vehicle’s suspension system with the capacity of 2.0L and below. The tube design is meant for the strut insert assembly where the user just need to replace the MR damper tube in the original strut housing. The result from the tests carried out on the prototype using the dynamic loading machine shows wider damping force range characteristic, as estimated during the design phase. Further simulation work were using the prototype characteristics data by applying it on a vehicle simulation model which shows that the MR damper are able to improve passenger ride comfort significantly. The development of MR damper prototype initiates the MR technology application in this country where previously the technology was not known very well in terms of automotive application.